(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Process of adoption ofprivatization policy gathered momentum at international level in 1979 when thenprime minister of England Mrs. Margaret Thatcher transferred BritishTelecommunication to private enterprise. In 1980 and 1985, “British GasCorporation”, “Rolls Royce” and “British Airways” were also privatized. In1981, United States of America adopted privatization. Similarly, France andItaly also adopted in one way or the other. In the wake of disintegration ofUSSR other socialistic economies at the beginning of the last decade of thetwentieth century, the tendency of privatization among world economies has beengaining ground. Besides, countries like Japan, Taiwan, South Korea, Hong Kong,Singapore, etc. also reveal that Privatization is the secret of their success. In India, afterindependence, our government had given much emphasis to public sector units.Hence 17 key industries were reserved for public sector in industrial policy1956. After 1991, our government realized that Public Sector units (PSUs) arenot operating efficiently. So government, in a phased manner, privatized somePSUs and at present, number of industries reserved for PSUs is reduced from 17to 2. Various loss making PSUs have been sold to private sector. Even in caseof profit making enterprises, partial disinvestments have been done to generatemore resources for modernization and development of these PSUs.